Biodiversity [videorecording] : the variety of life - Neitzal, Dal; Bullfrog films (Washington : Bullfrog Films, 1991)
Biodiversity: the variety of life offers a clear understandable explanation of the complex factors involved in conservation biology. Conventional approaches to species and habitat protection are plant life in our willderness areas. Biodersity introduces sveral new terms and concept, including'fragmentation, linkage and viable population.
Photographer, Daniel D. Dancer
Narrator: Mitch Friedman
Keywords: Biological diversity